BEaTS-α an open access 3D printed device for in vitro electromechanical stimulation of human induced pluripotent stem cells - David Cortes (Nature Portfolio, 2020)
Abstract 3D printing was used to develop an open access device capable of simultaneous electrical and mechanical stimulation of human induced pluripotent stem cells in 6-well plates. The device was designed using Computer-Aided Design (CAD) and 3D printed with autoclavable, FDA-approved materials. The compact design of the device and materials selection allows for its use inside cell incubators working at high humidity without the risk of overheating or corrosion. Mechanical stimulation of cells was carried out through the cyclic deflection of flexible, translucent silicone membranes by means of a vacuum-controlled, open-access device. A rhythmic stimulation cycle was programmed to create a more physiologically relevant in vitro model. This mechanical stimulation was coupled and synchronized with in situ electrical stimuli. We assessed the capabilities of our device to support cardiac myocytes derived from human induced pluripotent stem cells, confirming that cells cultured under electromechanical stimulation presented a defined/mature cardiomyocyte phenotype. This 3D printed device provides a unique high-throughput in vitro system that combines both mechanical and electrical stimulation, and as such, we foresee it finding applications in the study of any electrically responsive tissue such as muscles and nerves.